2022
DOI: 10.1021/acs.jpcc.1c08098
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Methanol Synthesis from CO2 Hydrogenation over Pt8/In2O3 Catalysts: A Combined Study on Density Functional Theory and Microkinetic Modeling

Abstract: In 2 O 3 -based catalysts have attracted considerable attention in CO 2 hydrogenation to methanol reactions, thanks to their excellent CO 2 conversion rate and methanol selectivity. In this work, density functional theory combined with microkinetic modeling is employed to investigate the methanol synthesis mechanism over a Pt 8 /In 2 O 3 catalyst. First, a stable Pt 8 /In 2 O 3 (110) catalyst is modeled, where the Pt 8 cluster is positively charged. Second, the adsorption properties of the reaction species are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The other is the ability to load metals onto In 2 O 3 to form In 2 O 3 -supported metal catalysts. 4,20−37 The metal catalysts investigated thus far include palladium (Pd), 4,[20][21][22]38,39 platinum (Pt), 4,[23][24][25]40 nickel (Ni), 4,33−36 ruthenium (Ru), 4,30 rhodium (Rh), 4,28,29 gold (Au), 4,26,27 silver (Ag), 4,32 iridium (Ir), 4,31 and cobalt (Co). 4,37 Most of these metals are normally not active catalysts for CO 2 hydrogenation to methanol but are good for CO 2 methanation (CO 2 + 4H 2 ⇋ CH 4 + 2H 2 O, ΔH°2 98 K = −165.0 kJ/mol; ΔG°2 98 K = −113.5 kJ/mol) or for the reverse water gas shift reaction (RWGS; CO 2 + H 2 ⇋ CO + H 2 O, ΔH°2 98 K = +41.2 kJ/mol; ΔG°2 98 K = +28.6 kJ/mol).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other is the ability to load metals onto In 2 O 3 to form In 2 O 3 -supported metal catalysts. 4,20−37 The metal catalysts investigated thus far include palladium (Pd), 4,[20][21][22]38,39 platinum (Pt), 4,[23][24][25]40 nickel (Ni), 4,33−36 ruthenium (Ru), 4,30 rhodium (Rh), 4,28,29 gold (Au), 4,26,27 silver (Ag), 4,32 iridium (Ir), 4,31 and cobalt (Co). 4,37 Most of these metals are normally not active catalysts for CO 2 hydrogenation to methanol but are good for CO 2 methanation (CO 2 + 4H 2 ⇋ CH 4 + 2H 2 O, ΔH°2 98 K = −165.0 kJ/mol; ΔG°2 98 K = −113.5 kJ/mol) or for the reverse water gas shift reaction (RWGS; CO 2 + H 2 ⇋ CO + H 2 O, ΔH°2 98 K = +41.2 kJ/mol; ΔG°2 98 K = +28.6 kJ/mol).…”
Section: Introductionmentioning
confidence: 99%
“…One is the need to seek other oxides like ZrO 2 to form a solid solution with In 2 O 3 , for stabilization and optimization of oxygen vacancies in In 2 O 3 . The other is the ability to load metals onto In 2 O 3 to form In 2 O 3 -supported metal catalysts. , The metal catalysts investigated thus far include palladium (Pd), , ,, platinum (Pt), , , nickel (Ni), , ruthenium (Ru), , rhodium (Rh), ,, gold (Au), ,, silver (Ag), , iridium (Ir), , and cobalt (Co). , Most of these metals are normally not active catalysts for CO 2 hydrogenation to methanol but are good for CO 2 methanation (CO 2 + 4H 2 ⇋ CH 4 + 2H 2 O, Δ H ° 298 K = −165.0 kJ/mol; Δ G ° 298 K = −113.5 kJ/mol) or for the reverse water gas shift reaction (RWGS; CO 2 + H 2 ⇋ CO + H 2 O, Δ H ° 298 K = +41.2 kJ/mol; Δ G ° 298 K = +28.6 kJ/mol). , The latter is also a competitive side reaction for CO 2 hydrogenation to methanol. Previous studies suggested that there is a strong interaction between In 2 O 3 and the metal; changing the electronic structure of the metal creates additional active metal/In 2 O 3 interfacial sites, making it become both highly active and selective toward CO 2 hydrogenation to methanol. ,, …”
Section: Introductionmentioning
confidence: 99%
“…A ∼12 Å vacuum was used. Oxygen vacancies play an important role in CO 2 activation, ,, and the vacancy at the O 1 atom was demonstrated to be favorable for CO 2 activation and hydrogenation . Two In atoms, In 2 and In 3 , were adjacent to each O v1 .…”
Section: Methodsmentioning
confidence: 99%
“…The insights derived from MKMs can serve as the basis for discovering new catalytic compositions with tunable structures possessing enhanced catalytic performance [45] . This can be attributed to its ability to reveal information such as degree of rate control (DRC), degree of selectivity control (DSC), and degree of chain growth control (DCGC), which are relevant parameters to simulate the kinetic behavior of the reaction system [48,49] . In the following paragraph, an attempt previously made to comprehensively describe CO 2 hydrogenation to higher hydrocarbons via DFT‐based MKM is described in detail.…”
Section: Mechanism Of Reactionmentioning
confidence: 99%